MODEL KEPEMIMPINAN DAN PERILAKU ORGANISASI PERSATUAN PERAWAT NASIONAL INDONESIA (PPNI) BALI TAHUN 1975-2016 - Dewa Arwidiana; I Wayan Gede Suacana; A. A. Rai Sita Laksmi (Public Inspiration : Jurnal Administrasi Publik, 2017)
The PPNI Bali organization established in 1975 should have enough time to implement the relevant organizational leadership model to be self-sufficient and have the legality of nursing care practices and professional recognition from the government. The purpose of this research is to understand the leadership model implemented in PPNI organization of Bali Province from 1975 - 2016 according to the period of leadership. This research was conducted in the working area of PPNI Bali organization with nine management of PPNI districts / cities in Bali with research object chairman, management and observer of PPNI Bali organization. The type of data used in this study are primary and secondary data, data obtained through observation, in-depth interview and documentation study. The results obtained that the leadership model of each periodization varies according to the concentration of conditions and situations that accompany during his leadership. Periodization 1975-2000 with directive leadership model, period of 2001-2005 leadership model participation and periodization 2006-2016 achievement-oriented leadership model. Each periodization with its leadership model describes the development and behavior of organizations that also vary.